2015
DOI: 10.5566/ias.1271
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for Porosimetry in Virtual Cementitious Composites to Economically and Reliably Estimate Permeability

Abstract: A novel methodology is described for porosimetry as well as for water transport through the pore system in dynamic DEM-based virtual cementitious materials. The pore network topology, the pore size distribution and the pore connectivity are assessed on the basis of a robotics-inspired pore delineation method and star volume measurements. Permeability estimates are based on a tube network model that incorporates these parameters and a shape factor. Since concrete contains in practical situations a variable amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The modelling framework presented in this study is validated against a wide range of experimental observation reported in Table. [2][3][4][5][6][7] In terms of improved accuracy as mentioned in lines 70-100 the accuracy of proposed methodology compared to previous studies that targeted modelling the same variables, is considerably more, to mention a few [1]- [4]. The main reason is that this study takes a wider range of pore size distribution into account compared to the majority of the studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The modelling framework presented in this study is validated against a wide range of experimental observation reported in Table. [2][3][4][5][6][7] In terms of improved accuracy as mentioned in lines 70-100 the accuracy of proposed methodology compared to previous studies that targeted modelling the same variables, is considerably more, to mention a few [1]- [4]. The main reason is that this study takes a wider range of pore size distribution into account compared to the majority of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…The framework consists of different modelling tools comprising, 121 microstructure modelling to model the microstructure and provide capillary PSD, particle 122 packing to estimate gel PSD, and pore network modelling, which integrates the entire range of 123 PSD and arrives at a statistically representative pore network, which is used as a basis to carry 124 out moisture transport calculations. In order to evaluate the capability of the proposed pore 125 network modelling framework, it is validated against an extensive set of existing experimental 126 data that includes a wide range of cementitious materials [1], [3] directly transferred to the network meaning that if the pore space consists of 0.5 gel pores and 166 0.5 capillary pores in terms of volume fraction then the same ratio in terms of volume fraction 167 would have to exist in the network as well. Therefore, the resulting network would be much 168 bigger (in terms of number of pores).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alternative of using virtual reality approaches should thus be given serious consideration. A reliable and quite economical methodology has been developed for that purpose by the present authors, and all the details are available in the literature (Li et al, 2015;Stroeven et al, 2015). These works also deal with alternative approaches employed in concrete technology and validation of the method using experimental and other numerical studies.…”
Section: Introductionmentioning
confidence: 99%
“…This paper concentrates exclusively on an elegant way of shortening the stage for quantitative assessment of the geometric properties of the main transport channels. The standard SVM, which has been analytically validated by Le (2015) and Li et al (2015), is used as a reference method. In general, 10 5 nodal points are required in a 100 μm cubic container to ensure reliable results.…”
Section: Introductionmentioning
confidence: 99%